Simulation of three phase induction motor in computer aided education / Ahmad Tajuddin Md. Ali - Md. Ali, Ahmad Tajuddin (2002)
This project is design for anyone especially for Electrical Engineering students to assist them in the process of learning the induction motor especially in the simulation of three phase induction motor. This project presents the Computer Aided Education (CAE) software. It was developed using Visual Basic (VB) programming language. Both text and graphics are included to provide simulation of induction motor program, interactive teaching notes, interactive diagrams and animated graphics, to make the learning process become understandable, interesting, assisting and improve the teaching and learning process.